PENERAPAN SANKSI ADMINISTRASI TERHADAP KETIDAKPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN BAGI WAJIB PAJAK (Studi Kasus Pada Dinas Pendapatan Daerah Kota Malang) - Azmi, Muhammad Razuli (Jurnal Mahasiswa Perpajakan, 2015)
This study attempts to know and comprehend sanctions that imposed against disobedience administration taxpayers to pay the tax of land and building, and to understand factors that inhibits the sanctions imposed against disobedience administration taxpayers to pay the tax of land and building. A method of this study is qualitative descriptive. The data used in this research is the data on primary and secondary data. Data collection techniques is in-depth interviews and documentation. The results of this study showed that the application of administrative sanctions against non-compliance of the paying tax of land and building in Malang has been runningwell. According to the Regional Regulation No. 11 of 2011, there were still unreceived SPT & PBB’s billing by taxpayer who didn’t pay yet. Influencing factors for administrative sanctions in Malang city was less of understanding for importance of taxation. Also there wasn’t shame yet if they didn’t pay the tax. Keyword: administrative sanction land and building tax, disobedienc